Control of Multi-Robot Arms in Object Retrieval Based on Human-Machine Interface - Rendyansyah Rendyansyah; Hera Hikmarika; Melia Sari; M. Al Furqon Syaidin Fikri; Ichlasul Akmali Rizky (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2024)
Multi-robot arm control is the result of the development of advanced robotics technology. With the advancement in the field of human-machine interface, controlling robot arms has become more efficient and can be done intuitively by humans. In this study, we designed three robot arms of 4-DoF, each of which is controlled by a computer in a visual program interface. This research aims to develop a human-machine interface-based multi-robot arm control system that allows humans to interact with the robots directly. The movement method of each robot uses Trajectory Planning, which works when the operator gives motion commands through the interface display. Multi-robot communication with a computer using USB hub serial format. The computer is the master, and each Arduino on the robot is the enslaved. Three robot arms have been tested and controlled by the HMI computer, and all of them move according to the commands of the operator. The time required by each robot to complete its mission is ± 10 seconds. The results of this study are expected to open new opportunities in the application of robotics in various fields, such as the manufacturing industry, health services, and transportation.